KETIDAKPASTIAN GOJEK DALAM DISKURSUS MASYARAKAT RESIKO - Moh. Mahdy Abyyu; Yunitasari Anggraeny; Velysa Novita Hariyanto (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Modern society is faced with risks inherent in its life. This risk comes from the technological uncertainty developments, especially in transportation modes. Gojek be a solution to the uncertainty several aspects by conventional transportation modes. This study uses a phenomenological approach, which places phenomena from the actors point of view and uses the risk society theory introduced by Ulrich Beck as an analytical tool. The concept used is reflective modernity and the boomerang effect that drivers and customers face respectively as users of the Gojek application. Informants are Gojek users consisting of customers as well as drivers. This research used interview, observation, and documentation techniques as primary data, while the secondary data used literature study techniques. Based on the results, it was found that several certainty factors were obtained by Gojek customers, including time, convenience, cost and security. This factor is referred to 'reflective modernity', where this factor becomes a reflection on the uncertainty of conventional transportation. However, for the record, security is also a risk if the goods ordered through Gojek are taken away by the driver. On the other hand, Gojek drivers get uncertainty risk factors, such as fictitious orders, and service discrepancies with customer ratings. This condition is referred to 'boomerang effect' where the risk returns to the main actor. As a solution, the company provides a feature to deal with fictitious orders and a rating feature by users.